A Comparative Study of Stability After the Installation of 2 Different Surface Types of Implants in the Maxillae of Dogs. Issue 5 (October 2015) - Im, Jae-Hyung; Kim, Su-Gwan; Oh, Ji-Su; Lim, Sung-Chul
Abstract : Purpose: This study was performed to investigate the histologic and histomorphometric findings of 2 different types of implant. Materials and Methods: Resorbable blasting media (RBM) and sandblasted with larger grit and acid etched (SLA) surfaced implants (24 fixtures in each group) were installed in posterior maxilla of dogs. The initial stability was measured using Periotest (Periotest value [PTV]). After 6 or 12 weeks, fixtures with surrounding bone were harvested. Results: The average initial stability of the SLA group (−1.71 ± 2.9) was higher than that of the RBM group (−1.25 ± 3.21), but there was no significant difference. The mean PTV of the RBM surface was higher than the SLA surface at 12 weeks. The average bone-implant contacts were 67.6% ± 16.0% at 6 weeks and 82.7% ± 8.6% at 12 weeks in the SLA group and 69.9% ± 17.6% at 6 weeks and 78.3% ± 9.2% at 12 weeks in the RBM group. Conclusion: The SLA and resorbable blasting media (RBM) surface implants demonstrated good stabilities and healing processes of the surrounding bone in the posterior maxilla. Therefore, the two domestic implants could provide predictable clinical results.